Precautionary and Liquidity Line : Operational Guidance Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
This note provides general guidance on the use of the Precautionary and Liquidity Line (PLL). After an overview of the instrument, explaining its specific nature, the operational issues are grouped into five areas: an outline of the process and specific steps that need to be followed if a member expresses interest in an arrangement; guidance on access, phasing, and purchases; guidance on determining qualification of a member and appropriate ex-post conditionality; and a guide to the semi-annual review process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet